Engineering Clostridium Strain to Accept Unmethylated DNA - Dong, Hongjun (Public Library of Science, 2010)
It is difficult to genetically manipulate the medically and biotechnologically important genus Clostridium due to the existence of the restriction and modification (RM) systems. We identified and engineered the RM system of a model clostridial species, C. acetobutylicum, with the aim to allow the host to accept the unmethylated DNA efficiently. A gene CAC1502 putatively encoding the type II restriction endonuclease Cac824I was identified from the genome of C. acetobutylicum DSM1731, and disrupted using the ClosTron system based on group II intron insertion. The resulting strain SMB009 lost the type II restriction endonuclease activity, and can be transformed with unmethylated DNA as efficiently as with methylated DNA. The strategy reported here makes it easy to genetically modify the clostridial species using unmethylated DNA, which will help to advance the understanding of the clostridial physiology from the molecular level.